ABSTRAK - PENGARUH KOORDINASI TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA SEKRETARIAT DAERAH KOTA KENDARI - Aslim, La Ode; Bakti, Bakti (Universitas Halu Oleo, 2019)
This study aims to determine the extent of the influence of coordination on employee work effectiveness at the Regional Secretariat of Kendari City. By using questionnaire data collection techniques, documentation and interviews with informants who are considered potential to provide information about the coordination system and work effectiveness at the Kendari City Regional Secretariat.Then to test the hypothesis, statistical analysis techniques are used through simple linear regression, which is to find out the relationship between the independent variables (X), namely coordination and non-independent variables (Y), namely the effectiveness of employees in Kendari City. Testing the hypothesis is used version 22 of the Statistics Package for Social Science (SPSS) program. The results of this study indicate that coordination has a significant influence on the effectiveness of Employee Work in the Regional Secretariat of Kendari City. The results of testing the Spearman-Brown Correlation coefficient indicate that coordination has a relatively large contribution to work effectively in the Regional Secretariat of Kendari City. This means that the better the coordination is carried out, the higher the work effectiveness of employees. In this study, it was also found that the implementation of the main tasks and functions of the ten sections and twenty-nine sub-sections had not been implemented properly.